The Study of Propylene Glycol Effect as Wetting Agent Content for Offset Printing Technique - Mawan Nugraha; Supardianningsih Supardianningsih; Henra N. Sukma; Susiani Susiani; Tan-Thanh Huynh (Universitas Andalas, 2023)
Although the printing offset technique offered the best printout quality among other printing techniques, however, there is a drawback of the offset technique which needs great skill to handle the process, i.e the presence of trace water molecules on the image area of the plate. The water’s existence in the image area leads to the poor covering of ink which makes the blurry printout than it must be. Therefore, we used various concentrations of propylene glycol such as 0%, 0.05%, and 0.1% as wetting agents to prevent the trace water sticks to the image area of the plate. We used the HVS paper 80 g/m2 as printing material and the machine of Oliver Sakurai 472 ED to study the role of propylene glycol. Propylene glycol has been considered based on stronger interaction with water molecules than the interaction of the image area - propylene glycol. By investigating the visual quality, density, and dot gain of the printout, we concluded that the wetting agent content of PG 0.05% (v/v) increased the visual brightness, and density of the printout, compared to the water only as the wetting solution.